Oil spill detection from Synthetic Aperture Radar Earth observations: a meta-analysis and comprehensive review. Issue 7 (3rd October 2021) - Jafarzadeh, Hamid; Mahdianpari, Masoud; Homayouni, Saeid; Mohammadimanesh, Fariba; Dabboor, Mohammed
ABSTRACT: Oil spills are one of the most hazardous disasters with significant short- and long-term effects on fragile marine ecosystems. Synthetic Aperture Radar (SAR) has been considered an effective technology for mapping and monitoring oil spills in the marine environment, primarily thanks to its weather-, illumination-, and time-independent capabilities. To cope with serious oil spill threats, researchers have developed various analytical methodologies utilizing key advantages of SAR imagery to identify the occurrence of oil spills and discriminate lookalikes. Choosing the appropriate SAR specifications and investigating the effects of field conditions are challenging for oil spill monitoring and should be investigated further. This paper presents a comprehensive review study on maritime surveying and oil slick detection using SAR imagery through indexed research studies' compilation and analysis. To this end, a total of 230 peer-reviewed papers, published in various remote sensing (RS) journals and 78 conference papers in the International Society for Photogrammetry and Remote Sensing (ISPRS) archive and the IEEE International Geoscience and Remote Sensing Symposium (IGARSS) proceedings were reviewed. Our review study represents a meta-analysis investigation of these papers focusing on several features, including data, sensor type, imaging mode, microwave carrier frequency (e.g., L-, C-, and X-bands), polarization option (i.e., single-pol, dual-pol, full-pol, and compact-pol), incidence angle, and wind speed. Furthermore, it provides an overview of the RS techniques developed to deal with the oil spill detection task. This paper can be a guideline for two groups of audiences; those interested in oil spill monitoring who want to get an overview of the problem and how to address it, and those already working in the field who want to understand the scope of the work being accomplished. Consequently, the current paper contributes both to academic RS research and to practical applications.